THE INFLUENCE OF CARDING PARAMETERS OPTIMIZATION ON THE USEFUL TIME COEFFICIENT OF A ROTOR SPINNING MACHINE - Lastochkin, Pavel (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article presents the results of a study aimed at optimizing the technological parameters of the spinning process using methods of mathematical experiment design and modeling. The main focus is on the influence of the speed regimes of the WEBFEED and IDF-2 systems of modern carding machines on the quality indicators of the carded sliver and yarn, particularly on the linear density irregularity. Experiments conducted under real production conditions made it possible to reduce the number of yarn breaks from 42 to 28 per 1000 spinning positions, increase the winding coefficient from 0.992 to 0.995, and increase the operational time coefficient from 0.979 to 0.988. As a result of implementing the optimized parameters, yarn quality significantly improved: irregularity decreased, breaking strength increased, and the number of defects was minimized. Based on the developed methodology, key operational indicators for the AUTOCORO 9 rotor spinning machine were calculated. It was established that the machine’s Useful Time Coefficient (UTC) increased from 0.95 to 0.97, and the Production Rate (PR) increased from 128.25 kg/h to 130.95 kg/h. The annual increase in yarn production volume per machine amounted to 22.68 tons. The obtained results confirm the high efficiency of applying mathematical modeling for improving both the technological and economic indicators of spinning production.